HUBUNGAN ANTARA EMOSI POSITIF YANG DIALAMI MAHASISWA DENGAN PRESTASI AKADEMIK PADA MAHASISWA FKIP UNILA TAHUN AKADEMIK 2011/2012 - Era Hidayah; Giyono Giyono; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of the research objective is the author wanted to determine therelationship between positive emotions that experienced by students with theacademic achievement of students FKIP Lampung University academic year2011/2012. The problem in this research is the low student academic achievement.The main problem in this research is "is the low academic achievement of students iscaused by positive emotional factors that experienced positive student?" . Themethod that used is the method of correlation. The population in this research werestudents of FKIP Lampung University with academic year of 2007, 2008, and 2009,which have a low GPA. While the study sample as many as 144 students. Datacollection techniques in this study using a questionnaire emotion PANAS-X (Positiveand Negative Affect Scale-X), which includes 35 kinds of emotions revealed that theresults was correlated with students' academic achievement such as IPK.The results obtained in this study there is a positive correlation between positiveemotions such as happy, joy, awe, excitement, gratitude. attentive, trying, amazed,relaxed, happy, inspired, passionate, courageous, interested, confident, full ofenergy, concentration, enthusiasm experienced by students toward academicachievement with a positive correlation coefficient of 0.272 and significant at thelevel 0.001 (0.001 is less than α: 0.005, Ha was accepted and Ho was rejected),which means that there is a relationship between positive emotions that experiencedby students with the students' academic achievement. The conclusion of this researchis there is a positive relationship between positive emotions experienced by studentswith the students' academic achievement. Suggestions in this study were collegestudent should try to regulate negative emotions with positive and constructiveattitude in order to obtain the process of maximum learning in study.Keywords: The relation of positive emotions, academic  achievement.